A Comparative Analysis of the Stability of Open-Deck River Boats Using Righting Moment and GM0 Based Criteria - Hasanudin, Hasanudin; Saputra, Aditya Dwi; Yulianto, Ardi Nugroho; Sujantoko, Sujantoko (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
The Musi River is an important transportation route in Indonesia, where traditional boats such as Jukungs and Keteks are widely used. Both are open-deck vessels, making stability a crucial factor for safety and operability. This study analyses and compares the stability of a Jukung and a Ketek in order to provide insights for safer traditional boat design. The methodology involves calculating the stability moment (MGZ) at a given heel angle and the heeling moment (MKR) due to turning and passenger distribution, based on Biro Klasifikasi Indonesia (BKI) and the GM₀ value specified by International Maritime Organization (IMO). Numerical simulations based on hull geometry are also applied for a more detailed assessment. Although similar in size, the Jukung has greater displacement owing to its flat U-shaped hull extending from top to bottom. Reducing passenger loads lowers the centre of gravity and increases the height of the righting lever. Both boats satisfy stability criteria across loading cases; however, the Jukung consistently demonstrates higher MGZ values, which increases further as the load decreases. Findings show that both vessels remain stable with MGZ exceeding MKR. The Jukung maintains a positive GM₀ under all loading conditions, whereas the Ketek fails to meet stability requirements at higher loads but is acceptable at reduced passenger levels. Overall, the Jukung proves more stable and safer, with its hull form providing a larger righting lever and greater safety margin than the Ketek. This highlights the critical role of hull design in ensuring traditional boat safety along the Musi River.